The effect of standing working attitude on work fatigue an musculoskeletal complaints in Midang Endek cloth craftsmen - Ida Ayu Sri Adnyani; I Ketut Wiryajati (PT WIM Solusi Prima, 2026)
Endek woven fabric is one of the artistic treasures of Indonesian culture. One of the processes in the production of woven fabric is the midang process, which involves winding threads onto a loom frame through repetitive layering and stacking of aligned threads. The midang process requires precision, speed, and repetition; the work is monotonous and performed while standing. To produce two to four midang results, artisans require two days. The method used was quantitative descriptive analysis, calculating the percentage (%) of questionnaire results using the Nordic Body Map questionnaire and 30 items of subjective fatigue measured on a four-point Likert scale, averaged from 20 midang artisans. The study results indicate an 83.8% increase in musculoskeletal complaints and a 67.0% increase in work-related fatigue following the work period, indicating that standing work postures affect workers’ conditions. Working in a standing position for prolonged periods on a regular basis can cause foot pain, swelling of the soles, lower back pain, and pain in the neck and shoulders. This can lead to cumulative trauma disorders (CTD). To reduce these issues, short breaks are needed between the morning and afternoon shifts. Short breaks can help minimize complaints while using the midang tool.